A conceptual paper: the study of competencies of tourism students towards their work experience - Jamaluddin, Ameer Firdaus; Saad, Mazni (2019)
Tourism Industry is an emerging industry that always change due to the tourists demands. Hence, the demand keeps evolving which resulting on the improvement of skills and knowledge of the key players. This study is to identify the competencies of tourism students towards their work experience. Apart from that, the emerging tourism industry really needs competent and suitable employers to continue the successfulness of the industry. As stated by Adeyinka-Ojo (2018), among the common barrier in the recruitment functions in the hospitality and tourism sector is the low frequency of basic skills. This shows that most of the tourism fresh graduates are incompetent where they are lacking even in the basic skills such as communication skills. A set of online questionnaire will be used in this study which then will be contributed to the fellow respondents. Besides, purposive sampling is used in this research study as the respondents have been acknowledged by the researcher which are the Tourism Planning and Hospitality Management from International Islamic University of Malaysia, IIUM. The results will then emphasis on the role of internship becoming the most efficient factors affecting this study as the internship is the most reliable platform for the fresh graduates to improve themselves to be more competent in the industry. Thus, the results of these findings will help to improve the competencies of tourism industries nevertheless helps to produce competent graduates that suit this emerging tourism industry. To add, it is recommended for future studies to include more industry despite only on the tourism industry in their study to have betterment in the combination of various industries to bring fortune towards the country’s economic status.